Meta-Analyses of Genome-Wide Association Data Hold New Promise for Addiction Genetics - Agrawal, Arpana (J Stud Alcohol Drugs, 2016)
Meta-analyses of genome-wide association study data have begun to lead to promising new discoveries for behavioral and psychiatrically relevant phenotypes (e.g., schizophrenia, educational attainment). We outline how this methodology can similarly lead to novel discoveries in genomic studies of substance use disorders, and discuss challenges that will need to be overcome to accomplish this goal. We illustrate our approach with the work of the newly established Substance Use Disorders workgroup of the Psychiatric Genomics Consortium.